The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1373/clinchem.2004.035253
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sensitive Immunoassays for Free and Total Human Glandular Kallikrein 2

Abstract: Background: Free and total human kallikrein 2 (hK2) might improve the discrimination between prostate cancer and benign prostatic hyperplasia. Concentrations of hK2 are 100-fold lower than concentrations of prostatespecific antigen (PSA); therefore, an hK2 assay must have a low detection limit and good specificity. Methods: PSA-and hK2-specific monoclonal antibodies were used in solid-phase, two-site immunofluorometric assays to detect free and total hK2. The total hK2 assay used PSA-specific antibodies to blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…Analysis of our study population, a reasonably representative cohort of 867 men from a contemporary population treated with radical prostatectomy for clinically localized PCa at a single institution, included fPSA and a recently published method for fhK2 detection (24 ). Previous studies indicated that a low ratio of fPSA to tPSA (%fPSA) is linked to advanced prostate pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of our study population, a reasonably representative cohort of 867 men from a contemporary population treated with radical prostatectomy for clinically localized PCa at a single institution, included fPSA and a recently published method for fhK2 detection (24 ). Previous studies indicated that a low ratio of fPSA to tPSA (%fPSA) is linked to advanced prostate pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, were not able to confirm these findings. The ratio of fhK2 to thK2 (%fhK2) has been previously measured in a set of 103 patients with PCa, in whom it ranged from 17% to 131% (mean, 81%) (24 ). However, no study has ever evaluated the clinical relevance of serum fhK2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study established, also, a reference interval for KLK6 serum levels in adults (145) . Moreover, Vaisanen et al developed a sensitive immunoassay with good specifi city for the accurate determination of free and total human kallikrein 2 (KLK2) concentration in the male bloodstream, as this might improve the discrimination between prostate cancer and benign prostatic hyperplasia (146) . tPSA and fPSA were also measured in the blood serum of patients with prostate cancer or BPH, using immunofl uorometric techniques (147) .…”
Section: Detection and Quantifi Cation Of Klks In Biological Fl Uidsmentioning
confidence: 99%
“…Recently, when differentiate expression of PIM-1 in normal prostate and PCa was analyzed by gene chip analysis, over-expression of PIM-1 in PCa has been demonstrated [5,6]. Human glandular kallikrein (hK2) is an androgen-regulated protein that has high identity with prostate-specific antigen (PSA) and is expressed almost exclusively in prostatic epithelial cells [7,8]. Although the expression of PSA has been found to be reduced in higher grade and presumably more biologically active disease, the expression of hK2 has been found to increase gradually from benign epithelium to prostatic intraepithelial neoplasia and to prostate cancer.…”
Section: Introductionmentioning
confidence: 99%